Struktur Argumentasi Penalaran Proporsional Mahasiswa dalam Menyelesaikan Comparison Problem Berdasarkan Strategi Penyelesaian - Hasna Inas Sadiya; Darmawan, Puguh (JUMAT: Jurnal Matematika, 2024)
This research aims to describe the structure of students' proportional reasoning arguments in solving comparison problems based on the solution strategy used. This research is qualitative research with a case study approach. The research subjects were three students from the Mathematics Education Study Program, State University of Malang, who were selected based on differences in solution strategies, namely unit rate, cross product algorithm, and additive. The instruments used were comparison problem tests and semi-structured interviews. The research results show that students with the unit rate strategy are able to fulfill all elements of argumentation in the form of claims, evidence, and reasoning. Students with the cross product algorithm strategy are able to provide claims and evidence but cannot express logical reasoning. Meanwhile, students with an additive strategy are only able to provide correct claims without supporting evidence and reasoning. These findings indicate that argumentation of the strategies used in proportional reasoning can represent conceptual understanding